Distributed Database Systems in Vehicular Ad-Hoc Network - Jan Janech; Tomas Baca (Communications - Scientific letters of the University of Zilina, 2010)
The article introduces basics of classic Distributed Database System (DDBS) and explains its unsuitability for dynamically changing networks such as Vehicular Ad-hoc Network (VANET). Thus a concept of a new architecture is proposed. This new architecture is designed for use in mobile networks as it solves problems of classic architecture, however as explained at the end of the article, it has some limitations of its own.